2005
DOI: 10.1111/j.0307-6962.2005.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold tolerance in relation to developmental and adult temperature in a butterfly

Abstract: Abstract.  Larvae of the butterfly Lycaena tityrus (Poda) are reared at 20 or 27 °C until adult eclosion, after which they are maintained at the same temperature or are transferred to the alternate temperature. The resulting adults are exposed to −20 °C for 8 min, returned to ambient temperature, and the recovery time to standing position is recorded. On the day of eclosion, individuals reared at 20 °C show 19% shorter recovery times than individuals reared at 27 °C. This effect of developmental temperature di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…These two nested ANOVAs present complimentary perspectives on the relative importance of plasticity type and treatment temperature for variation in each of the traits. Previous work demonstrated that the effects of developmental plasticity can be altered following adult acclimation for several traits (Fischer et al, 2003;Zeilstra and Fischer, 2005). Therefore we expected equal contributions of plasticity types to total variance.…”
Section: Statistical Analysesmentioning
confidence: 83%
See 4 more Smart Citations
“…These two nested ANOVAs present complimentary perspectives on the relative importance of plasticity type and treatment temperature for variation in each of the traits. Previous work demonstrated that the effects of developmental plasticity can be altered following adult acclimation for several traits (Fischer et al, 2003;Zeilstra and Fischer, 2005). Therefore we expected equal contributions of plasticity types to total variance.…”
Section: Statistical Analysesmentioning
confidence: 83%
“…Nonetheless, strong opposing responses to high and low temperature treatments for lower thermal limits have been found in several other studies, though typically these examined acclimation effects on a single stage only (e.g. Ayrinhac et al, 2004;Hoffmann et al, 2005b;Klok and Chown, 2003;Slabber and Chown, 2005;Terblanche et al, 2005b;Zeilstra and Fischer, 2005). Likewise, asymmetric or threshold effects of treatment temperature have previously been recorded for T crit,max (Hoffmann et al, 2005b;Klok and Chown, 1998;Slabber and Chown, 2005), metabolic rate (Hoffmann, 1985;Terblanche et al, 2005a) and desiccation rate (Rourke, 2000).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations